OVARIES HEMODYNAMICS FEATURES AFTER HYSTERECTOMY AT THE WOMEN OF REPRODUCTIVE AGE - Lipchanskaya, G.N.; Kvashenko, V.P.; Golubyatnicov, I.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The condition blood flow in ovaries and their volume at 360 women is investigated which have transferred hysterectomy in reproductive age and at 30 healthy women. The connection of infringements blood flow in ovarian artery with age surveyed, duration after operation of the period, presence and character after operation of complications is investigated. The role of infringements blood flow in development syndrome of an exhaustion ovaries is shown and is specified on presence of the factors causing polycystic changes in ovaries operation of the women.